2017
DOI: 10.1371/journal.pone.0172911
|View full text |Cite
|
Sign up to set email alerts
|

PTEN expression as a predictor for the response to trastuzumab-based therapy in Her-2 overexpressing metastatic breast cancer

Abstract: BackgroundEven though trastuzumab is an effective therapy in early stage Her-2+ breast cancer, 40–50% of advanced Her-2+ breast cancer patients develop trastuzumab resistance. A potential resistance mechanism is aberrant downstream signal transmission due to loss of phosphatase and tensin homologue (PTEN). This study investigated the relationship between the expression of PTEN and trastuzumab response in Her-2 overexpressing metastatic breast cancer patients.MethodsBetween 2000 and 2007, 164 patients with Her-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Also, a reduced or absent of PTEN expression in breast cancer tissue was only in 28 out 85 of breast cancer patients (33%) in the Engin et al, (2006) study, which was using IHC for the detection of PTEN. There were other studies did not correspond to our data in this study, and reported decreased or absent PTEN expression in breast carcinoma tissue in high percentage among the breast cancer patients (Kechagioglou et al, 2014;Gschwantler-Kaulich et al, 2017;Shabbir et al, 2017). As listed in Table 2, PTEN expression did not have any relation to any clinicopathological factors (P>0.05), there were also some studies that showed no association between PTEN expression and clinicopathological factors of breast cancer.…”
Section: Discussioncontrasting
confidence: 62%
“…Also, a reduced or absent of PTEN expression in breast cancer tissue was only in 28 out 85 of breast cancer patients (33%) in the Engin et al, (2006) study, which was using IHC for the detection of PTEN. There were other studies did not correspond to our data in this study, and reported decreased or absent PTEN expression in breast carcinoma tissue in high percentage among the breast cancer patients (Kechagioglou et al, 2014;Gschwantler-Kaulich et al, 2017;Shabbir et al, 2017). As listed in Table 2, PTEN expression did not have any relation to any clinicopathological factors (P>0.05), there were also some studies that showed no association between PTEN expression and clinicopathological factors of breast cancer.…”
Section: Discussioncontrasting
confidence: 62%
“…In addition to its role in the suppression of cell proliferation and migration, PTEN is well known for its function in modulating cancer cell responses to drug treatment (24,25). In NSCLC, promoter methylation was initially reported to account for PTEN silencing, with ~35% of PTEN-negative NSCLC patients exhibiting high levels of promoter methylation (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the number of HER2+ patients in this study was very small ( n = 23), the results should be interpreted with care. Moreover, there are reports on the relationship between PTEN expression and response to the trastuzumab-containing therapy in HER2+ breast cancer [ 21 ]. In summary, comprehensive studies on the potential biomarkers of HER2+ GC, whether they be clinical or molecular, are still lacking and need to be pursued.…”
Section: Discussionmentioning
confidence: 99%